Influence of biotechnical applications on the physiological, mechanical and chemical properties of potential slope plants / Mohammed Saifuddin - Mohammed, Saifuddin (2014)
Slope plant helps to stabilize the masses of soil via hydrological and mechanical means. The effects of vegetation on soil depend on the overall root growth, development, chemical composition and its mechanical functions. Thus, this study aimed to investigate the impact of biotechnical applications on the physiological, mechanical and chemical properties of selected tropical plants. Initially four legume trees, Leucaena leucocephala, Adenanthera pavonina, Peltophorum pterocarpum and Pterocarpus indicus, were screened for their physiological performance and root profiles. The best two species, L. leucocephala and P. pterocarpum, were further evaluated in terms of physiological, mechanical and chemical properties. The enhancement of these properties was also evaluated using biotechnical applications: phytohormones and stem cutting. The results showed that phytohormone application improved physiological performances of both L. leucocephala and P. pterocarpum. In terms of root profiles, phytohormone increased root initiation, length and volume which ultimately enhanced the bioengineering function of L. leucocephala and P. pterocarpum. In the shear box study, phytohormone treated plants showed a higher soil shear strength and residual strength than those of the non-treated plants. Additionally, the soil cohesion factor was enhanced by 62% and 102% in treated L. leucocephala and P. pterocarpum, respectively. In relation to root chemical content, treated L. leucocephala showed a spectacular higher holocellulose and alpha-cellulose content by 17.9% and 20.7%, respectively, than treated P. pterocarpum. The root holocellulose content and soil shear strength was positively correlated (r = 0.86), indicating that an increased in root holocellulose content would result in the enhancement of soil-root reinforcement. In terms of revegetation through stem cutting, L. leucocephala was not found to be feasible. Unlike L. leucocephala, P. pterocorpum was successfully propagated via stem cutting, exhibiting a higher survival rate and root initiation of treated stem. A higher Leaf Area Index (LAI) and root biomass was observed in treated basal cutting than in treated apical cutting. Moreover, phytohormone treated cutting showed increments in vegetative growth, root length and soil matric suction. In conclusion, biotechnical approaches significantly improved the physiological, mechanical and chemical properties of the species studied which in turn, led to the enhancement of the soil-root reinforcement capacity of potential slope plants.